2011
DOI: 10.1523/jneurosci.4794-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid Receptors in the Nucleus Accumbens Shell Region Mediate the Effects of Amphetamine on Inhibitory Control But Not Impulsive Choice

Abstract: Acute challenges with psychostimulants such as amphetamine affect impulsive behavior in both animals and humans. With regard to amphetamine, it is important to unravel how this drug affects impulsivity since it is not only a widely abused recreational drug but also regularly prescribed to ameliorate maladaptive impulsivity. Therefore, we studied the effects of amphetamine in two rat models of impulsivity, the five-choice serial reaction time task and the delayed-reward task, providing measures of inhibitory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 77 publications
(122 reference statements)
5
57
1
2
Order By: Relevance
“…The dose range of AMPH used here engenders significant hyperactivity and robustly increases responding in PR and other operant tasks when infused into the Acb (Bakshi and Kelley, 1991;Kelley and Delfs, 1991;Zhang et al, 2003), in clear contrast to the lack of effects seen in the present study. With regard to impulsive action, systemic infusion of AMPH provokes premature responding in the five-choice serial reaction time task; this effect is blocked by intra-Acb dopamine antagonist infusions, naloxone infusions, or 6-hydroxydopamine lesions (Cole and Robbins, 1989;Pattij et al, 2007;Wiskerke et al, 2011). Furthermore, intra-Acb AMPH infusion strongly elevates inefficient DRL responding (Neill, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The dose range of AMPH used here engenders significant hyperactivity and robustly increases responding in PR and other operant tasks when infused into the Acb (Bakshi and Kelley, 1991;Kelley and Delfs, 1991;Zhang et al, 2003), in clear contrast to the lack of effects seen in the present study. With regard to impulsive action, systemic infusion of AMPH provokes premature responding in the five-choice serial reaction time task; this effect is blocked by intra-Acb dopamine antagonist infusions, naloxone infusions, or 6-hydroxydopamine lesions (Cole and Robbins, 1989;Pattij et al, 2007;Wiskerke et al, 2011). Furthermore, intra-Acb AMPH infusion strongly elevates inefficient DRL responding (Neill, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, it is possible that SB 242084 facilitated methylphenidate-induced enhanced DA signalling in the striatum in a manner similar to that observed for the psychostimulant cocaine (Navailles et al 2004). The antiimpulsivity profiles of methylphenidate and SB 242084 are matched by d-amphetamine (Wiskerke et al 2011) and it is hypothesized that the dopaminergic effects of d-amphetamine are responsible (van Gaalen et al 2006), most likely in the striatum. Thus, it appears likely that the DDT is sensitive to altered DA overflow in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified distinct dopaminergic pathways for impulsive action and impulsive choice (Pattij & Vanderschuren, 2008 ;Winstanley et al 2006). More recently, naloxone was shown to attenuate amphetamine-induced increased impulsive action, but had no effects of amphetamine-induced attenuation of impulsive choice (Wiskerke et al 2011). In utero nicotine exposure was also shown to disrupt 5-CSRTT performance in adult rats, including increased Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Naltrexone also reduced amphetamine subjective effects in non-dependent and amphetamine-dependent subjects, and reduced amphetamine abuse in a placebo-controlled doubleblind clinical trial (Jayaram-Lindstrom et al, 2008a;JayaramLindstrom et al, 2008b;Jayaram-Lindstrom et al, 2004). However, opioid antagonists do not block all amphetamine effects (van Kammen and Schulz, 1985;Winslow and Miczek, 1988;Wiskerke et al, 2011;Woolfolk and Holtzman, 1997), and it is unknown whether opioid mechanisms contribute to the anti-cocaine effects of amphetamine. Overall, research on these or other possible amphetamine mechanisms may suggest new strategies to dissociate the anti-cocaine effects of amphetamine from its undesirable effects.…”
Section: Investigate the Generality And Mechanisms Of Agonist Medicatmentioning
confidence: 99%